2000
DOI: 10.1034/j.1600-0463.2000.d01-24.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localisation of IGF‐binding protein mRNAs in regenerating rat skeletal muscle

Abstract: The expression of the insulin-like growth factor-binding proteins (IGFBP) -3, -4, -5 and -6 was investigated in neonatal, in normal adult and in regenerating rat skeletal muscle. Semi-quantification was done by densitometric scannings of Northern blots. The expression of all investigated IGFBPs, with the exception of IGFBP-5, was higher in neonatal than in adult muscle. During postischaemic regeneration the expression of all IGFBPs increased, but with different time schedules. IGFBP-3 increased transiently dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…IGFBP-4 has a unique expression profile consisting of a lower mRNA abundance in starved fish, followed by a transitory but strong increase 1 day after refeeding. Given that in muscle, IGFBP-4 mRNA has been detected in connective tissue instead of muscle fibers (Jennische & Hall 2000), our observations suggest that the transitory increase of IGFBP-4 mRNA does not participate in myogenesis resumption.…”
Section: Discussionmentioning
confidence: 82%
“…IGFBP-4 has a unique expression profile consisting of a lower mRNA abundance in starved fish, followed by a transitory but strong increase 1 day after refeeding. Given that in muscle, IGFBP-4 mRNA has been detected in connective tissue instead of muscle fibers (Jennische & Hall 2000), our observations suggest that the transitory increase of IGFBP-4 mRNA does not participate in myogenesis resumption.…”
Section: Discussionmentioning
confidence: 82%
“…Expression of IGFBP-4 was correlated with that of IGF-I, and IGFBP-4 expression was the highest of all the binding proteins measured in fast muscle. IGFBP-4 is also known to be highly expressed in mammalian connective tissue (Boes et al, 1992;Jennische and Hall, 2000). Knudtson and colleagues reported that a C-terminal basic region of 20 amino acids was required for targeting the rat IGFBP-4 to connective tissue (Knudtson et al, 2001).…”
Section: Igf Signalling During Feedingmentioning
confidence: 99%
“…Northern blot analysis revealed that IGFBP-4 mRNA is widely expressed in adult rat tissues, including adrenal gland, testis, spleen, heart, liver, lung, kidney, stomach, hypothalamus and brain cortex, with liver being the site of the highest expression (Shimasaki et al 1990). The expression of IGFBP-4 was also examined in rat small intestine (Shoubridge et al 2001), smooth muscle (Smith et al 2001), skeletal muscle ( Jennische & Hall 2000), pancreas (Hill et al 1999), uterus and placenta (Cerro & Pintar 1997), mouse spinal cord (Arnold et al 2000), mouse and human thymus (Li et al 1996), human prostate (Thomas et al 2000), bone (Mohan et al 1995a) and ovary (Zhou & Bondy 1993, el Roeiy et al 1994) of several species. In the mouse embryo, IGFBP-4 transcripts were detected as early as 11 days postcoitum (dpc) in different regions, including telencephalon, mesencephalon, snout, tongue and differentiating sclerotomes.…”
Section: Igfbp-4 Expression In Vivo and Its Regulationmentioning
confidence: 99%